2014
DOI: 10.1021/la404290c
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Magnetite Formation: From Biocombinatorial Approaches to Mineralization Effects

Abstract: Biological materials typically display complex morphologies and hierarchical architectures, properties that are hardly matched by synthetic materials. Understanding the biological control of mineral properties will enable the development of new synthetic approaches toward biomimetic functional materials. Here, we combine biocombinatorial approaches with a proteome homology search and in vitro mineralization assays to assess the role of biological determinants in biomimetic magnetite mineralization. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 48 publications
(112 reference statements)
5
66
1
1
Order By: Relevance
“…Further studies with Mms7ct indicate that it and other Mms proteins may play a more significant role in controlling magnetite mineral structure than previously hypothesized. Beyond simple control of size and shape of magnetite (29,30), they may also template the crystal lattice of the mineral itself similar to what has been observed with calcium biomineralization, where unstable crystal forms and phases of the mineral are stabilized by interaction with peptides and other macromolecules (1,2). In the specific case of iron minerals, lattice stabilization could also affect the redox potential of individual Fe atoms within the mineral.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Further studies with Mms7ct indicate that it and other Mms proteins may play a more significant role in controlling magnetite mineral structure than previously hypothesized. Beyond simple control of size and shape of magnetite (29,30), they may also template the crystal lattice of the mineral itself similar to what has been observed with calcium biomineralization, where unstable crystal forms and phases of the mineral are stabilized by interaction with peptides and other macromolecules (1,2). In the specific case of iron minerals, lattice stabilization could also affect the redox potential of individual Fe atoms within the mineral.…”
Section: Discussionmentioning
confidence: 88%
“…In addition to redox partners that are necessary to generate both Fe(II) and Fe(III), there also exist small magnetosome proteins proposed to template mineralization by direct binding to the material (28) analogous to the more wellunderstood mineralization of calcium. These Mms proteins were identified by their tight association with the magnetite nanoparticles isolated from magnetotactic bacteria and have been shown experimentally to be able to control mineral shape in vitro through their highly acidic C-terminal sequences (29,30). Similar to other magnetotactic bacteria, the MAI of AMB-1 contains multiple mms genes, mms5 (mamG), mms6, and mms7 (mamD), which have been previously shown to possess overlapping genetic function as all genes must be deleted to observe the resulting biomineralization defect (12).…”
Section: Mineralization Of Iron Oxides From Fe(ii) With Magnetosome Pmentioning
confidence: 99%
“…While such processes lead to the formation of SSD particles, imaging by transmission electron microscopy (TEM) has shown the particles to be widely dispersed in size due to aggregation20. The use of additives was reported to control the mechanism of magnetite formation and possibly the resulting nanoparticle dimensions2122232425. Here, we show that the addition of polyarginine mostly leads to the formation of 40 nm monodisperse magnetite particles that are made from 10 nm sub-domains, yet possess true SSD properties.…”
mentioning
confidence: 70%
“…21 VSM showed that the saturation magnetization (M s ) was 77 Am 2 /kg and that the coercivity (H c ) was 8 mT (Figure 7c), which reflect the decrease in the average crystal size as compared to the control (Figure 3e). The same Table 1, entry (a) 4, (b) 1, (c) 5, (d) 2, (e) 8, (f) 7 and (g) 3, which demonstrate that all crystal sizes between ∼15 nm and ∼60 nm are accessible through the manipulation of the experimental conditions.…”
Section: Crystal Growth and Designmentioning
confidence: 93%